ESTUDO SOBRE TRANSFERÊNCIA DE CALOR EM PAREDES COMPOSTAS POR BLOCOS CERÂMICOS E DE CONCRETO - Kohler, Raquel; Spohr, Valdi H.; Garcia, Emmanuelle S. H.; Pasche, Eduardo; Flora, Cristiano S. D. (Salão do Conhecimento, 2013)
Resumo